CURRENT THERAPY OF THE RESTLESS LEGS SYNDROME - Suat Acar,; Ahmet Murat Gencer, (Archives of Rheumatology, 2005)
RLS (Restless legs syndrome) is a sensorimotor disorder characterized by an urge or need to move the limbs usually associated with sensory and motor symptoms, chronic progressive or relapsing remitting course and prevalance increase with age. The treatment of RLS include the treatment of secondary causes such as iron deficiency anemia, periferic neuropathy, diabetes, üremia. L-DOPA (L-Dihydroxyphenylalanine) is the first line drugs for treatment of both primary and secondary RLS patients. % 50 percent of patients may develop augmentation (worsening of RLS symptomps in the course of therapy) by L-DOPA therapy. Dopamine agonists such as pergolide, pramipexole, ropinirole, cabergoline are dopaminergic agents used in the treatment of RLS. Opioids, benzodiazepines and anticonvulsants such as gabapentin can be considered when dopamine agonists not respond or not tolerable by patients. The current therapy of RLS include drugs which are effective on longterm usage and yet have minimal adverse events and safety.